Dossier de presse sur l'homosexualité. - Groupe de Libération Homosexuel Politique et Quotidien (GLHPQ) (Paris : Savelli, 1977)
Fonds Suzan Daniel (FSD)
Fonds Suzan Daniel (FSD)F/97/001
Frans
Monografie